Pharmaceutical care in the use of medicinal plants with anti-hypertensive action in the elderly (Research, Society and Development, 2021)
Hypertension is a highly prevalent cardiovascular disease among the elderly population, representing an expressive risk factor for morbidity and mortality. Based on empirical knowledge, a large part of this population uses medicinal plants to treat illnesses such as hypertension. The objective was to identify in the literature the main medicinal plants with anti-hypertensive potential used by the elderly in the treatment of hypertension, highlighting the importance of pharmaceutical care in therapy. The research was carried out in Scielo, BVS, PubMed and Google Academic in the period between 2011 and 2021, in Portuguese, English and Spanish. 45 articles were selected and 7 species of medicinal plants with antihypertensive potential were chosen. Allium sativum, Camellia sinensis, Cymbopogon citratus, Ginkgo biloba, Hibiscus sabdariffa, Panax ginseng and Zingiber officinale showed pharmacological actions in the control of hypertension. The indiscriminate use of these species can cause adverse effects such as intestinal gastric discomfort, hepatotoxicity and headache, hemorrhagic and cardiovascular events. In addition, the species, Ginkgo biloba, Hibiscus sabdariffa, Panax ginseng and Zingiber officinale showed drug interactions with antiplatelet and/or anticoagulant and antiepileptic drugs. In view of the risks presented, especially in the elderly, pharmaceutical care represents a potential therapeutic tool, evidenced in pharmacotherapeutic monitoring, guidance in the form of preparation, collection and storage of medicinal plants, facilitator of treatment adherence, educator and prescriber in the prevention of chronic diseases such as hypertension, promoting the rational use of medicinal plants with antihypertensive properties.